The Role of Celebrities in Contemporary Activism: The #SayHerName Movement as a Case Study - Tian, Zhirui (Transactions on Social Science, Education and Humanities Research, 2025)
This paper uses the #SayHerName movement as a case study and examined how online activism gained momentum once well-known artists, athletes, and actors supported it publicly. Throughout the case study process, a small sample of their social-media posts were collected and compared against the efforts of activists themselves. The material suggests that celebrity power pushed the names of Black women, such as Breonna Taylor, far beyond activist circles, pulled the campaign into public vision, and steered money and political focus towards related court cases and memorial funds. However, it also sometimes overshadowed underrepresented voices and drew the public attention on a limited number of tragic stories. This paper attempted to argue that celebrity endorsements could be effective if they facilitate opportunities for grassroots leaders instead of dominating the spotlight. It contributes to debates on digital protest and highlights the need for further research: tracking whether the momentum holds once the cameras move on).